Optimization of Supplementary Protein Milk Tablet Formulation for Rural School Children under Her Royal Highness Princess Maha Chakri Sirindhorn’s Project - Mayurachat Natvaratat,; Penkwan Chompreeda,; Vichai Haruthaithanasan,; Hathairat Rimkeeree, (Agriculture and Natural Resources, 2007)
Milk tablet formulated under Royal Chitralada Projects has been used as a tool to encourage more dairy consumption for Thai children. This study was conducted to develope milk tablet with high nutritive value for rural school children under Her Royal Highness Princess Maha Chakri Sirindhorn’s Project. An optimum formula of milk tablet with high nutritive value was formulated to minimize cost and maximize protein and energy, was accepted by primary school children and could be produced using processing facilities at the Royal Chitralada Projects. Main ingredients were whole milk powder, dried egg yolk powder (DEY), containing 35% rice flour, and sugar. The optimum formula consisted of 25% DEY, 55% milk powder, 15% sugar, 0.4% cab-o-sil, 1% talcum, 3.5% comprecel and 0.1% strawberry flavor. The high nutritive value milk tablet contained 15.8% protein and 22.9% fat which were higher than the regular formula. School children (n=50) from Her Royal Highness Princess Maha Chakri Sirindhorn’s Project at Phu-Fa Pattana village, Nan Province evaluated 20 tablets each using star picture 9-point hedonic scale. They rated overall liking as “like very much” (mean score was 8.8 from 9).